Physical education, study of 3º the education in the towns of Torre de Moncorvo and Vila Nova de Gaia - Ruben Gonçalves Pereira; José Luís Soidán (Desafio Singular, 2008)
The aim of this study that we proposed to develop was fundamentally guided as an attempt to answer a group of relevant questions: Is living in the interior of a country a restraining factor for the harmonious physical, mental and social development of the youth? Are physical aptitudes profiles distinct in terms of the level, depending on the fact that young people live in the interior or in the coast of a country? To answer these questions we develop a study in which we characterize and evaluate students of both sexes, from the 2nd and 3rd cycles of the Basic Education (from 5th to 9th grade), from schools of two diametrical opposed areas of Portugal: one school in a city by the coast - Vila Nova de Gaia, the other in the deep interior of Portugal - Torre de Moncorvo and we search the existence or not of an influence on the students' levels of physical aptitudes. This exploratory study was made from a random sample composed of 3271 subjects from the 5th grade to the 9th school grades. The battery of tests applied were the ones designated as "FACDEX" - Somato-Motor Development and Sports Excellence factors in the Portuguese Population. (Marques et al., 1991), obtaining a detailed analysis of the levels of Physical Aptitudes of young people from 10 to 17 years old. The results allowed us to conclude that the students of the Rural areas present a slightly higher standard in the Upper strength tests (2 kg ball), Medium strength (Sit Up's) and Lower strength (Long jump). The students of the Urban Zone present higher standard levels in the Flexibility tests (Sit and Reach), Upper strength (Hockey ball Launching"); "Dinamometry"; quickness "10x5 Metres." and "Resistance 12". In terms of Speed, they show identical values. The students of the Urban Zone show higher weight values in terms of age in the female and male sex, with the exception of male individuals from the 14 to 16 years old and the girls after 15 years old. The girls of the Rural Environment show superior body mass rates during all school grades, with the exception of the 8th grade.